STUDENTS’ PERCEPTIONS AND CHALLENGES TOWARD THE USE OF SMALL GROUP DISCUSSION METHOD: A STUDY IN EZPZ ENGLISH COMMUNITY - Hursan, Nur Husfiratie Hikmah Binti; Munir, Munir; G, Hasriani (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study explores students' perceptions and challenges related to the use of the Small Group Discussion (SGD) method in a non-formal English learning context, specifically in the EZPZ English Community in Makassar, Indonesia. Using a qualitative descriptive approach, data were collected through in-depth interviews with nine students from three different proficiency levels: beginner, basic, and intermediate. The findings reveal that most students have a positive perception of SGD, appreciating the enjoyable learning atmosphere, increased confidence, and opportunities for interaction. However, several challenges also emerged, such as dominant participants, a lack of vocabulary, and difficulties understanding discussion topics. These challenges are categorized into internal and external factors. The study emphasizes the importance of ability-based grouping in enhancing student comfort and engagement during SGD in non-formal education settings.